Associating or Disrupting: The Dutch Supreme Court’s Struggle in Prohibiting a Controversial Association - Jasper Doomen; Gelijn Molier (Rule of Law Studies Journal, 2026)
Background:  The prohibition of controversial associations presents a persistent challenge for democratic societies seeking to balance freedom of association with the protection of vulnerable individuals. This challenge is illustrated by the Dutch Association Martijn litigation, which raised fundamental questions concerning the legal justification for restricting associational freedom under the European Convention on Human Rights (ECHR). Aim: This article aims to examine the reasoning adopted by the Dutch courts, particularly the Dutch Supreme Court, in prohibiting Association Martijn and to evaluate whether the legal justification for the restriction is consistent with democratic principles, freedom of association, and the requirements of the ECHR. Method: The study employs a normative legal research design using doctrinal, human rights, and legal-philosophical approaches. The analysis is based on judicial decisions from the Association Martijn litigation, relevant provisions of the Dutch Civil Code, ECHR jurisprudence, and scholarly literature concerning freedom of association, public order, legal moralism, and child protection. Results: The analysis reveals that the central disagreement among the Dutch courts concerned not the importance of protecting children but the legal threshold required to justify restrictions on associational freedom. While the Court of Appeal required evidence of societal disruption, the Dutch Supreme Court treated child protection and harm prevention as sufficient grounds for intervention. The findings further demonstrate that harm and societal disruption represent analytically distinct justificatory frameworks and should not be treated as interchangeable bases for restricting freedom of association. Conclusion: The article concludes that restrictions on controversial associations require courts to identify clearly the specific justification relied upon and to satisfy the evidentiary threshold associated with that justification. By distinguishing more carefully between harm, public order, majority morality, and child protection, courts can strengthen both the protection of fundamental freedoms and the legitimacy of preventive state intervention in democratic societies.